The Effect of Competence and Career Development on Managerial Performance: Work Motivation as a Mediator (Empirical Study at the Primary Tax Service Office in South Sulawesi) - Mayairani Nurdiana, Triasmi; Randa, Fransiskus; Ng, Suwandi (AJAR, 2026)
This study aims to empirically investigate the influence of competence and career development of account representatives on managerial performance. The influence was tested both directly and indirectly through work motivation. The research model was built within the framework of self-determination theory. Data were collected from account representatives from all Primary Tax Service Offices in South Sulawesi using purposive sampling. Online questionnaire was applied to collect data. Data analysis was carried out through multiple regression and Sobel test. The results of the study reveal that competence and the career development of account representatives influence work motivation as well as managerial performance. Further testing using the Sobel test reveals that work motivation mediates the influence of both competence and career development on managerial performance. The results of the study support the self-determination theory of how individuals have the drive to improve their performance based on their experiences with the process of developing competence and their careers in the organization.